2017
DOI: 10.7771/2157-9288.1148
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Integrating Engineering in STEM Units and Student Achievement Gains

Abstract: This study examined different approaches to integrating engineering practices in science, technology, engineering, and mathematics (STEM) curriculum units. These various approaches were correlated with student outcomes on engineering assessment items. There are numerous reform documents in the USA and around the world that emphasize the need to incorporate engineering into science education. The authors of this study contend that different approaches to integrating engineering in STEM units correlate to larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…Some quantitative studies are found to have investigated the influence of the EDP on students' scientific structures and transfer situation (Chase, Malkiewich, & Kumar, 2019); students' participation, interest, and self-concept (Capobianco, Yu, & French, 2014); and students' knowledge (Chao et al 2017). Furthermore, Crotty et al (2017) in their study tested the difference in students' achievement, comparing the class that received engineering lessons at the beginning with the one given at the end. In addition, some researches using mixed methods is also found.…”
Section: Introductionmentioning
confidence: 99%
“…Some quantitative studies are found to have investigated the influence of the EDP on students' scientific structures and transfer situation (Chase, Malkiewich, & Kumar, 2019); students' participation, interest, and self-concept (Capobianco, Yu, & French, 2014); and students' knowledge (Chao et al 2017). Furthermore, Crotty et al (2017) in their study tested the difference in students' achievement, comparing the class that received engineering lessons at the beginning with the one given at the end. In addition, some researches using mixed methods is also found.…”
Section: Introductionmentioning
confidence: 99%
“…However, planning locally situated, design-based learning experiences takes cognitive focus as well as more time and coordination of resources and will likely generate stress among teachers related to managing an open-ended learning experience (Shernoff et al, 2017). To address these challenges, I-STEM leaders should help teachers build their confidence and ability to implement PBL effectively, become knowledgeable about design and engineering pedagogical practices and principles (e.g., Crotty et al, 2017;Cunningham & Lachapelle, 2014), and dedicate time for collaborative curriculum and instructional development. Administration, 2015, p. 14).…”
Section: Curriculum and Instructionmentioning
confidence: 99%
“…They found that "student achievement was significantly correlated to science GPA, but not significantly [correlated] to mathematics or communication GPA" (p. 37). The study by Crotty et al (2017) correlated "different approaches to integrating engineering practices in science, technology, engineering, and mathematics (STEM) curriculum units . .…”
Section: Research Question 3: Impact Of Engineering Design On Studentsmentioning
confidence: 99%